Mental health among adolescents from returned portuguese immigrant families - Felix Neto (2010)
This study investigated mental health problems and their predictors among adolescents from returned immigrant families. The sample consisted of 360 returned adolescents (mean age = 16.8 years; SD = 1.9). The mean duration of a sojourn in Portugal for the sample was 8.2 years (SD = 4.5). A control group of 217 Portuguese youths were also included in the study. Adolescents from immigrant families reported mental health levels similar to those of Portuguese adolescents who have never migrated. Girls showed more mental health problems than boys. Younger adolescents showed fewer mental health problems than older adolescents. Adaptation variables contributed to mental health outcomes even after acculturation variables were accounted for. Implications of the study for counselors are discussed.